AN ANALYSIS OF THE VALIDITY OF ENGLISH TEST MADE BY THE TEACHER IN SMP NEGERI 1 BONTOMARANNU - Nur' Islamiyah Umar; Erwin Akib; asrianto (FKIP Unismuh Makassar, 2022)
This study aims to determine whether the English test made by the teacher is in accordance with the content validity. To determine the content validity, the researcher compare the English test with the syllabus, lesson plan, and the material that has been taught. This study uses a qualitative descriptive method by using document analysis in the form of mid- semester test and interview from the teacher. This research collects data from English teacher who teaches in seventh grade in SMP Negeri 1 Bontomarannu.The results obtained after analysis the test made by the teacher, a total of 15 questions were made by the teacher who teaches in seventh grade in the mid- semester test. There are 13 questions that are categories accordance with the content validity, namely according to the syllabus, lesson plan, and the material that has been taught. While there are 2 questions that are categories as not accordance with the content validity. And from the results of interview, it can be concluded that the teacher made a grid of questions before making test. Test made by the teacher must be in accordance with the syllabus, lesson plan, and the material that has been taught and according to the level of student ability.